2016
DOI: 10.3168/jds.2015-10600
|View full text |Cite
|
Sign up to set email alerts
|

An observational study using blood gas analysis to assess neonatal calf diarrhea and subsequent recovery with a European Commission-compliant oral electrolyte solution

Abstract: An observational study was conducted on dairy calves (51 healthy, 31 with neonatal diarrhea) during outbreaks of diarrhea on 4 dairy farms. Clinical assessment scores (CAS) were assigned to each healthy and diarrheic calf [from 0 (healthy) to 4 (marked illness)]. Blood gas analysis [pH, base excess (BE), Na(+), K(+), Ca(2+), Cl(-), glucose, total hemoglobin, standard HCO3(-), strong ion difference (SID), and anion gap (AG)] was completed for each calf. Repeated measurements were taken in healthy animals, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 19 publications
5
61
0
1
Order By: Relevance
“…Adopting current blood gas reference ranges for healthy adult cattle (Divers and Peek, 2007;Stämpfli et al, 2012; to assess any blood gas derangements in neonates may be unwise, as differences exist between the ranges presented here and for adult bovines (Divers and Peek, 2007;Stämpfli et al, 2012;). This agrees with previous studies, which outlined similar findings regarding standard ranges for neonates (Rice, 1994;Gustin et al, 1997;Lorenz et al, 2005;Sayers et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Adopting current blood gas reference ranges for healthy adult cattle (Divers and Peek, 2007;Stämpfli et al, 2012; to assess any blood gas derangements in neonates may be unwise, as differences exist between the ranges presented here and for adult bovines (Divers and Peek, 2007;Stämpfli et al, 2012;). This agrees with previous studies, which outlined similar findings regarding standard ranges for neonates (Rice, 1994;Gustin et al, 1997;Lorenz et al, 2005;Sayers et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…These variations can influence the physiology of the calf, thus affecting their normal biochemical and hematological values. Furthermore, it has been shown that newborn calves, in a high-infection pressure environment, can have significantly lower mean blood gas values compared with calves in disease-free environments (Sayers et al, 2016). Whereas we made selection efforts to reduce the effect of this variable, it may be impossible to eliminate it under normal husbandry conditions and could account for year and farm effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kertz et al (1984) also reported an insignificant ef-fect of offering drinking water to newborn dairy calves on diarrhea. Disturbed electrolyte homeostasis in the blood, dehydration (as indicated by high blood Hct), and reduced blood pH (indicative of metabolic acidosis) are the most significant consequences of diarrhea in calves (Sayers et al, 2016). Blood HPT concentration has been identified as a useful tool in evaluating health status of dairy calves (Ganheim et al, 2007;Balikci and Al, 2014).…”
Section: Health Statusmentioning
confidence: 99%